DNA analýza AZF oblasti Y chromozómu u Slovákov s poruchou plodnosti - Behulová, Regína; Strháková, E; Boronová, I; Bernasovký, I; Bernasovská, J; Konecný, M; Repiská, V (Ceska gynekologie, 2010)
OBJECTIVE: Study on Y chromosomal AZF region deletions in Slovak population, application of DNA technique. DESIGN: Genetic-prospective study. SETTING: Institute of Medical Biology, Genetics and Clinical Genetics, Faculty of Medicine, Comenius University in Bratislava. METHODS: For detecting microdeletions in the Y-chromosomal AZF region in men with fertility disorders and for identifying Y-specific sequences we used the method of polymerase chain reaction (PCR) with using three different sets of sY sequences. For a verification of the specific type of deletion we used also fluorescently labeled kit. RESULTS: Diagnoses of referred patients were divided into 2 groups: azoospermia, oligospermia. In the followed-up group of 822 patients there were 349 patients with azoospermia, 473 patients with oligospermia. Globally we reported 38 cases of deletions in the AZF region of the Y chromosome, i.e. 4.62%. 24 patients with deletion are from the group of patients with azoospermia, i.e. 6.88%, 14 patients are from the group of patients with oligospermia (2.95%). Considering particular types of deletions we recorded deletions in each region, AZFa, AZFb and AZFc, combinated AZFbc deletion, but also a complete deletion of the whole AZF region. CONCLUSION: The study confirmed that detection of microdeletions of the AZF region is significant from diagnostic and prognostic view and it pointed out the importance of selection criteria for selecting patients.
Keywords: Humans; Azoospermia; Sequence Analysis, DNA; genetické lokusy; mužská infertilita; lidský chromozom Y; dospělí; lidé; Oligospermia; sekvenční analýza DNA; Adult; azoospermie; Seminal Plasma Proteins; Male; Chromosomes, Human, Y; chromozomální delece; Chromosome Deletion; polymerázová řetězová reakce; oligospermie; Polymerase Chain Reaction; Infertility, Male; proteiny semenné plazmy; mužské pohlaví; Genetic Loci